Chemical Adjustment of Fibrinolysis - Alexey M. Shibeko; Ivan S. Ilin; Nadezhda A. Podoplelova; Vladimir B. Sulimov; Mikhail A. Panteleev (MDPI AG, 2024)
Fibrinolysis is the process of the fibrin-platelet clot dissolution initiated after bleeding has been stopped. It is regulated by a cascade of proteolytic enzymes with plasmin at its core. In pathological cases, the balance of normal clot formation and dissolution is replaced by a too rapid lysis, leading to bleeding, or an insufficient one, leading to an increased thrombotic risk. The only approved therapy for emergency thrombus lysis in ischemic stroke is recombinant tissue plasminogen activator, though streptokinase or urokinase-type plasminogen activators could be used for other conditions. Low molecular weight compounds are of great interest for long-term correction of fibrinolysis dysfunctions. Their areas of application might go beyond the hematology field because the regulation of fibrinolysis could be important in many conditions, such as fibrosis. They enhance or weaken fibrinolysis without significant effects on other components of hemostasis. Here we will describe and discuss the main classes of these substances and their mechanisms of action. We will also explore avenues of research for the development of new drugs, with a focus on the use of computational models in this field.